Boundary Criteria for the Stability of Delay Differential-Algebraic Equations - Leping Sun; Yuhao Cong (Abstract and Applied Analysis)
This paper is concerned with the asymptotic stability of delay differential-algebraic equations. Two stability criteria described by evaluating a corresponding harmonic analytical function on the boundary of a certain region are presented. Stability regions are also presented so as to show the method geometrically. Our results are not reported.